Analysis of Behaviour of E-learning Users by Unified Teory of Acceptance and Use of Technology (UTAUT) Model A Case Study of Vocational Education in Halu Oleo University - St. Nawal Jaya; Muh. Naidzirin Anshari Nur; Arman Faslih; Muh. Nadzirin Anshari Nur (Jurnal Vokasi Indonesia, 2017)
E-learning (EL) as a supporting tool in learning process has increasingly developed because the implementation of the tool will be helpful for both lecturers and students to be more interactive in delivering materials and to evaluate learning outcomes. Analysis of the user’s behavior was required to measure the success rate of the implementation of e-learning. One of the models used in the present study was Unified Theory of Acceptance and Use of Technology (UTAUT). The model was designed to explain the behavior of the users on the information technology. The main variable was behavioral intention with four elements namely performance expectancy, effort expectancy, social influence and facilitating conditions. Data were collected randomly from the students of vocational education, university of Halu Oleo by distributing questioners to the e-learner users. The data were then validated and analyzed using regression analysis. The results showed EL affected the behavioral intention, performance expectancy, effort expectancy, social influence and facilitating conditions.